EVALUASI PROGRAM PENGEMBANGAN KARIR GURU MELALUI KEGIATAN KKG DALAM PENINGKATAN KINERJA SD ISLAM NURUL HUDA DAN SDIT SYAMSUL ULUM - Al Juska Sasni Akbar; Canra Muhammad Kadfi; Wawan Karsiwan (Administrasi Pendidikan Umbara Bogor, 2024)
Teachers play a crucial role as determinants of the success of learning conducted in the classroom. The inability of teachers to implement effective teaching can negatively impact the quality of learning experienced by students. As an effort to improve teacher performance, the government has introduced a new initiative by providing a teacher career development program through the KKG (Kelompok Kerja Guru or Teacher Working Group). To assess whether this program is effectively implemented, an evaluation is necessary. This evaluation is conducted at Sekolah Dasar Islam Nurul Huda and SDIT Syamsul Ulum. The type of research used is a qualitative approach with a context, input, process, and product (CIPP) evaluation model. In this method, data collection is conducted through observation, interviews, documentation, and questionnaires as supporting data for the research findings. The evaluation results show: (1) Context: The teacher career development program through KKG activities is a need for teachers and serves as a platform for self-development. Furthermore, it is a program fully supported by the school principal as an effort to improve teacher performance and to help address issues that arise during the teaching and learning process. (2) Input: This shows that the KKG program meets the needs of teachers, seen from aspects of human resources, materials, and training received, as well as easy access to necessary facilities. (3) Process: The program is conducted according to the allotted time. (4) Product: The product of the KKG activities is an improvement in the quality of teaching staff, which ultimately positively impacts students' learning outcomes. Therefore, this teacher career development program through KKG activities will certainly continue and receive ongoing support from the school principal with improvements in certain areas.